Improving Students' Motivation in Learning Physics through Group Discussion Method at SMA Negeri 16 Makassar (Jurnal Pendidikan Fisika, 2019)
The research  included Classroom Action Research with the aim knew increased motivation learning physics through group discussion method. Classroom Action Research was carried out  at The Eleventh MIA 1gradeof sixteen state senior high school of Makassar. The research  consisted of two cycles. The first cycle consisted of two actions and the second cycle also consists of two actions. The procedure carried out in each cycle consists of planning, implementation, observation, and reflection. For getting the data used the observation sheet and the results of test scores in each cycle. The data analysis technique used is descriptive analysis and qualitative analysis. The results showed that the learning motivation of students in physics learning at The Eleventh MIA 1grade of sixteen state high school of Makassar could be improved by using group discussion methods. Based on the results of the questionnaire the motivation learning physics students in the second cycle of learning motivation to learn physics began. Students look more cheerful, enthusiastic in participating in learning. Evidently in the work of the LKPD, all group members jointly worked on the activities that existed at the LKPD, each group competing asked when there was something that was not yet understood in the LKPD, because all groups wanted the best group.Keywords: Learning Motivation, Group Discussion, Classroom Action ResearchPenelitian ini termasuk Penelitian Tindakan Kelas dengan tujuan untuk mengetahui peningkatkan motivasi belajar fisika melalui metode diskusi kelompok pada peserta didik. Penelitian Tindakan Kelas dilaksanakan di SMA Negeri 16 Makassar kelas XI MIA 1. Penelitian ini terdiri dari dua siklus. Siklus pertama terdiri dari dua tindakan dan siklus kedua juga terdiri dari dua tindakan. Prosedur yang dilaksanakan pada setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Untuk mendapatkan data digunakan lembar observasi dan hasil nilai tes pada setiap siklus. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa motivasi belajar peserta didik pada pembelajaran fisika di kelas XI MIA 1 SMA Negeri 16 Makassar dapat ditingkatkan dengan menggunakan metode diskusi kelompok. Berdasarkan hasil angket motivasi belajar fisika peserta didik pada Pada siklus II motivasi belajar fisika peserta didik mulai terlihat. Peserta didik terlihat lebih ceria, antusias dalam mengikuti pembelajaran. Terbukti dalam pengerjaan LKPD, semua anggota kelompok secara bersama-sama mengerjakan kegiatan yang ada pada LKPD, setiap kelompok berlomba-lomba bertanya ketika ada sesuatu yang belum difahami pada LKPD, karena semua kelompok menginginkan gelar kelompok terbaik.Kata kunci: Motivasi Belajar, Diskusi Kelompok, Penelitian Tindakan Kelas